Activity Of Non Productive Coal Powder and It's Humic Matter Extract with Fertilizer to Improve Soil Chemistry Properties Of Ultisol - Yusnaweti MP (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
-